1984
DOI: 10.1136/bmj.289.6455.1345
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of cardiotocography in predicting baby's condition at birth.

Abstract: Highlanders were also less likely than other respondents to report having consumed alcohol in the previous week. Levels of alcohol consumption-Table IV shows the mean levels of alcohol consumption reported by men and women in the three areas. Significant differences were reported in the mean amounts consumed during the previous week by both sexes in the three areas. Among men, those in Tayside drank the most; whereas among women, those in Kent were the heaviest drinkers. Highlanders drank the least. These diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The prerent results, however, apply to clearly defined and marked abnormalities, all of which arose at least 3 h before death and did not resolve or remit. The application of continuous monitoring as a routine in all labours remains at best controversial and is often unwanted by women in labour (MacDonald et al 1985;Kelso et al 1978;Curzen et al 1984;Niswander et al 1984). When, however, there is pnor evidence of substantial risk of fetal distress in labour, these Several factors were not found to be associated with perinatal death in this group, although they may have been suspected on the basis of previous evidence (Morris & Heady 19SSa, 19SSb;Heady et al 19S5a, 19556;Daly el al.…”
Section: Present and Previous Findingsmentioning
confidence: 99%
“…The prerent results, however, apply to clearly defined and marked abnormalities, all of which arose at least 3 h before death and did not resolve or remit. The application of continuous monitoring as a routine in all labours remains at best controversial and is often unwanted by women in labour (MacDonald et al 1985;Kelso et al 1978;Curzen et al 1984;Niswander et al 1984). When, however, there is pnor evidence of substantial risk of fetal distress in labour, these Several factors were not found to be associated with perinatal death in this group, although they may have been suspected on the basis of previous evidence (Morris & Heady 19SSa, 19SSb;Heady et al 19S5a, 19556;Daly el al.…”
Section: Present and Previous Findingsmentioning
confidence: 99%
“…They found that the diagnosis of fetal distress has a low positive predictive value. Subsequent studies [2,10] and a retrospective study within the European Community Concerted Action project 'Perinatal Monitoring' addressing a series of consecutive data from seven European university clinics showed a low sensitivity and a high false-positive (FP) rate in all centers [4]. None of the studies published reached 95% sensitivity, which has been proposed as a general minimum sensitivity for diagnostic tests [11].…”
Section: Introductionmentioning
confidence: 98%
“…Current techniques for fetal surveillance during labor and delivery consist of mainly cardiotocography (CTG), ST‐analysis of the fetal ECG (STAN) and fetal scalp blood sampling. These techniques involve a risk of both over‐ and underestimation of fetal hypoxia, with unnecessary operative intervention and/or hypoxic injury to the fetus as possible consequences17.…”
Section: Introductionmentioning
confidence: 99%